Enhancing Student Learning Outcomes in Science Through Environmental-Based Instructional Videos in Grade V at SD Inpres 5 Taipalaga - Rizal, Rizal; Surahman, Surahman; Rosola, Rosola; Aqil, Moh.; Pahriadi, Pahriadi (FKIP - Universitas Riau, 2025)
This study aimed to improve student learning outcomes in the Science, Environment, and Social Studies subject through the use of instructional videos supported by elements of the surrounding natural environment in Grade V of SD Inpres 5 Taipalaga. The research employed a quantitative approach using classroom action research, conducted in two cycles consisting of four stages: planning, action, observation, and reflection. The sample and population consisted of 16 students. Data were collected through essay-type achievement tests and observational instruments. The results from Cycle I showed that 11 out of 16 students achieved the minimum mastery criteria, resulting in a classical completeness rate of 68.75%. In Cycle II, 12 students met the learning objectives, increasing classical completeness to 75%, an improvement of 6.25% over Cycle I. Student activity observations also improved from 72.91% in Cycle I to 89.58% in Cycle II. Likewise, teacher performance increased from 85.71% to 96.42% across the two cycles. These findings demonstrate that integrating instructional videos with local environmental contexts can enhance student engagement and understanding of science concepts. Therefore, the use of environmentally assisted video learning is an effective strategy to improve learning outcomes in IPAS for elementary school students.